2015
DOI: 10.5152/balkanmedj.2015.15101
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E Mutation, RET/PTC1 and PAX8-PPAR Gamma Rearrangements in Follicular Epithelium Derived Thyroid Lesions - Institutional Experience and Literature Review

Abstract: Background: Thyroid cancers are the most frequently occurring endocrine malignancy worldwide. In Turkey, thyroid cancers are ranked 2 nd on the incidence list in women, with a rate of 16.2%, but they are not included among the top 10 cancer types in men. Aims: To identify the contribution of the BRAF V600E mutation, and the RET/PTC1 and PAX8-PPARγ rearrangements in the diagnosis and differential diagnosis of follicular epithelial-derived thyroid lesions. Study Design: Retrospective clinical and molecular genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…BRAF mutations in TC have been vigorously investigated since the early 2000s (17,18). The frequency of the BRAF V600E mutation reportedly ranges from 32 to 80% in patients with PC (4,(19)(20)(21). Several large-scale multicenter studies reported that the average frequency of the BRAF V600E mutation in PC is approximately 48% (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…BRAF mutations in TC have been vigorously investigated since the early 2000s (17,18). The frequency of the BRAF V600E mutation reportedly ranges from 32 to 80% in patients with PC (4,(19)(20)(21). Several large-scale multicenter studies reported that the average frequency of the BRAF V600E mutation in PC is approximately 48% (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The PAX8/PPARγ fusion gene is most commonly found in FTC, the follicular variant PTC, and benign follicular adenomas, though the prevalence of these rearrangements varies significantly among studies. The mean frequency in FTC is 5.6% in Asia, 43.8% in the Americas, and 27.4% in Europe ( Table 4 ) [ 36 38 45 46 73 74 75 76 77 78 79 80 81 82 83 84 ]. The low frequency of PAX8/PPARγ rearrangements in Asia is particularly noteworthy, with one Japanese study failing to identify a single PAX8/PPARγ rearrangement in FTC [ 73 ].…”
Section: Pax8/pparγ Rearrangementmentioning
confidence: 99%
“…The loss of NF-1 protein function leads to increased RAS signaling. The BRAF kinase molecule is also a downstream RAS effector, and its mutations are found in numerous cancers such as melanomas and thyroid carcinomas (11,20). New advances in molecular pathology have provided information that specific mutations are associated with particular tumors, but BRAF mutation can be expected in malignant melanomas but also can be found in common melanocytic nevi.…”
Section: Discussionmentioning
confidence: 99%